2001
DOI: 10.1159/000047401
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Ultrafiltration for Chronic Congestive Heart Failure: Rationale, Evidence and Future

Abstract: Peritoneal dialysis (PD) was the first dialytic therapy used to achieve euvolemia in individuals with refractory congestive heart failure. PD remains a viable therapy for the short-term management of refractory congestive heart failure, and fluid removal rates comparable to those obtained with the continuous extracorporeal therapies can be achieved. However, with advances in extracorporeal therapies, the role of PD in these situations is limited to those individuals in whom vascular access cannot be obtained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…This therapy is experimental and only anecdotal reports are available. 31 We used an intermittent, automated, cycler-driven approach. Ultrafiltration effectively treated our patient's refractory edema and improved her symptoms.…”
Section: Dialysis As a Treatment Optionmentioning
confidence: 99%
“…This therapy is experimental and only anecdotal reports are available. 31 We used an intermittent, automated, cycler-driven approach. Ultrafiltration effectively treated our patient's refractory edema and improved her symptoms.…”
Section: Dialysis As a Treatment Optionmentioning
confidence: 99%
“…Several other studies have also demonstrated more effective fluid removal with ultrafiltration with the limitation of a diuretic only control arm [29][30][31][32] . This benefit was also shown with the utility of peritoneal dialysis in Mehrotra et al, Khalifeh et al and Sanchez et al [15][16][17] . In addition there was an added benefit of regaining diuretic sensitivity in PD use which was also demonstrated in our case series where 5 out of 6 of our patients had a reduction and improved diuresis with lower doses of diuretic therapy [15] .…”
Section: Discussionmentioning
confidence: 82%
“…It is associated with high morbidity and mortality with average documented survival of 50% at 6 months [10] . With improved understanding of the physiology and techniques of peritoneal dialysis, ambulatory peritoneal ultrafiltration can be applied to the management of refractory heart failure in addition to conventional diuretic therapy with favourable outcomes [11][12][13][14][15][16][17][18] . The main advantages of ambulatory peritoneal ultrafiltration over conventional haemodialysis for fluid removal include less dysrhythmias, haemodynamic fluctuations and fluid shifts [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…70 In clinical practice, the feasibility of efficient fluid removal by peritoneal ultrafiltration has been shown by several studies. 71 In a case report by Maxwell et al, 72 up to 1063 mL/h of ultrafiltration was achieved with the use of this technique. The present data, however, are limited to small observational studies and cases without a control group.…”
Section: Peritoneal Ultrafiltrationmentioning
confidence: 96%